Evaluación del uso de robóts humanoides para estimular la motricidad gruesa en niños de 3 a 5 años del CDIM la Condamine - Bravo Barre, Jandyr Adrian (2023)
The purpose of the current study was to evaluate humanoid robotic prototypes for the stimulation of gross motor skills in children between the ages of 3 and 5. Because motor development is crucial in the early years of school, it aims to test an engaging and novel approach to teaching. Through educational robotics, it is known that in Ecuador the technology for the stimulation of gross motor skills at an early age is very limited and expensive, so the main objective of the research is to evaluate the use of DIY humanoid robots as a stimulation tool. of gross motor skills in children from 3 to 5 years of the Municipal Child Development Center (CDIM) "La Condamine". The research method is experimental and descriptive, therefore the operation of this project is based on two humanoid robotic prototypes where the Master device is only used by the teacher who completed the movements taught by the Berges-Lezine Gesture Imitation Test to measure the stimulation of gross motor skills, these are replicated by the slave device which works only with the students, on the other hand, the communication between the prototypes occurs through bluetooth technology for it, sending and collecting information in such a way that it is obtained data that is processed to verify that this new teaching methodology helps as support material for teachers and improves the work of stimulation of gross motor skills. The results obtained demonstrate that the students who worked with the robotic prototypes were able to achieve the ideal score, which was determined by the Berges-Lezine gesture imitation test to be 8 points in 3-year-olds and 15 points in 4-year-olds, obtaining in 3-year-old children 8.83 points and in 4-year-old children 12.93 points. The system can therefore be utilized as a gross motor stimulation tool, even though it enables 3-year-olds to surpass their target score and 4-year-olds to reach a respectable score.